2020
DOI: 10.1111/geb.13071
|View full text |Cite
|
Sign up to set email alerts
|

Human‐associated species dominate passerine communities across the United States

Abstract: Aim Human development and agriculture can have transformative and homogenizing effects on natural systems, shifting the composition of ecological communities towards non‐native and native species that tolerate or thrive under human‐dominated conditions. These impacts cannot be fully captured by summarizing species presence, as they include dramatic changes to patterns of species abundance. However, how human land use patterns and species invasions intersect to shape patterns of abundance and dominance within e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 68 publications
1
15
0
Order By: Relevance
“…There may be autocorrelation between routes as nearby routes are likely to share avian species. However, sensitivity analyses using spatially thinned datasets and plotting of residuals over space suggested that the level of autocorrelation at the route scale was low in this dataset (Sofaer et al, 2020, Supplementary Materials).…”
Section: Real Data Examplesmentioning
confidence: 98%
See 3 more Smart Citations
“…There may be autocorrelation between routes as nearby routes are likely to share avian species. However, sensitivity analyses using spatially thinned datasets and plotting of residuals over space suggested that the level of autocorrelation at the route scale was low in this dataset (Sofaer et al, 2020, Supplementary Materials).…”
Section: Real Data Examplesmentioning
confidence: 98%
“…The song bird dataset comprises data collected in a recently published study on how human land use patterns impact the proportional abundance of synanthropic species, which benefit from an association with humans, within song bird communities in the conterminous United States (Sofaer et al, 2020) based on North American Breeding Bird Survey (BBS) (Pardieck et al, 2017) data from 2010 to 2012. The dataset has 1649 rows with each row corresponding to one survey covering a 24.5‐mile route.…”
Section: Real Data Examplesmentioning
confidence: 99%
See 2 more Smart Citations
“…Much research has been devoted to documenting and quantifying negative impacts of anthropogenic land use changes on wildlife, such as declines in density and local extirpation of populations (Crawford & Bolen, 1976; Wilberg et al., 2011), lower fitness of individuals (Li et al., 2016; Slabbekoorn & Ripmeester, 2008), reduced genetic diversity (Holderegger & Di Giulio, 2010; Miraldo et al., 2016), and behavioral changes (Andersen et al., 2017; Longcore & Rich, 2004). A major outcome of broad‐scale anthropogenic land use change is the loss of habitat specialists and gain of habitat generalist and synanthropic species (including invasive species), with the consequent homogenization of wildlife communities (Clavel et al., 2010; Sofaer et al., 2020).…”
Section: Introductionmentioning
confidence: 99%